A CRITICAL REVIEW ON AVALEHA KALPANA - S, *Mahesh; Karalam B, Sheela; S, Aravind; S Pillai, Neethu (International Journal of Ayurveda and Pharma Research, 2018)
Avaleha is the most common secondary Kalpana (dosage form) which has been employed in various disorders and this product is gaining popularity due to its easy administration, palatability and longer shelf life. It is a semisolid preparation of herbal drugs prepared in decoction or extracts of different herbs by adding sweetening agents like jaggery, sugar or sugar candy. The component drugs which are used in the preparation of Avaleha are aqueous medium, substrate, Oushada dravyas, lipid medium, additives etc. By analyzing consistency of various Avaleha varies from freely-flowing, paste-like, semisolid and granular, which depends upon the substrate and Oushada churna ratio. Avaleha can be compared to confections because both contains essential ingredients as sugar and water and optional ingredients as edible oils, honey, flours, starches, edible salts etc. Avaleha are intend to provide better drug absorption through the oral cavity along with absorption through villi. The literature related to Avaleha has been surveyed from various Ayurvedic literatures, journals, Ayurvedic Formulary of India etc. and presented briefly here. Here we have discussed the information regarding Avaleha like ingredients, method of preparation, Avaleha paka lakshana, non-conformances related to Avaleha production, comparison between Avaleha and confections and absorption.